Atopic Dermatitis as a Paradoxical Effect of Secukinumab for the Treatment of Psoriasis - Eduardo V. Mendes Roncada; Victoria Romanini Brambilla; Beatriz Freitas Filitto; Mariana Pirajá Genta; Marilda Ap. M. Morgado de Abreu (Karger Publishers, 2021)
In the therapeutic arsenal to treat moderate to severe psoriasis, the new agents are secukinumab and ustekinumab, which are fully human monoclonal antibodies, directed against IL-17A and IL-12/23, respectively, which have been shown to be effective and safe in several studies. Their side effects are rare, and the most frequently reported side effects were infection, especially nasopharyngitis, headache, pruritus, high blood pressure, and low back pain. Unlike the side effects, the paradoxical reaction can be defined by the appearance or exacerbation of a pathological condition that usually responds to a certain class of drug. The appearance of this reaction in patients using anti-interleukins is poorly described; however, as they are new drugs, they may be more common than the literature reports. We describe a case of a paradoxical reaction, with the appearance of atopic dermatitis, after using secukinumab to treat psoriasis.